Analisis Implementasi Kebijakan Manajemen Risiko dalam Penyusunan APBD di Badan Pengelolaan Keuangan Daerah Provinsi DKI Jakarta - Afriandy, Rendy; As'ad, Muhammad (Neraca : Jurnal Akuntansi Terapan, 2025)
Strong risk management resulting from good management and proper guidelines can ensure that the accuracy of handling will be more guaranteed. However, there are still complaints from the public in the implementation of the Regional Revenue and Expenditure Budget (APBD) of the DKI Jakarta Provincial Government. The purpose of this study is to analyze and evaluate the Implementation of Risk Management Policies in the Preparation of APBD at the Regional Financial Management Agency of DKI Jakarta Province. In writing this thesis, the author used a qualitative research approach. The conclusion of this study is that the Implementation of Risk Management Policies in the Preparation of APBD at the Regional Financial Management Agency of DKI Jakarta Province has not been able to run well because the standards and targets of risk management integrated into each stage of the APBD preparation process have not fully run according to the rules, less than optimal performance is shown by stakeholders in the risk identification evaluation. Apart from that, the lack of competent resources, understanding, number (of employees) and communication with socialization causes stakeholders not to understand the implementation of risk management and the irresponsible attitude of some stakeholders in risk management reporting and SOPs are not carried out in accordance with the regulatory format.